Anemia Hemolitik Autoimun pada Anak - Bella Kurnia; Theatania Trisna Yonathan (Cermin Dunia Kedokteran, 2019)
Anemia hemolitik autoimun (AIHA) disebabkan oleh antibodi terhadap eritrosit sendiri yang menyebabkan hemolisis dan anemia. Penyebab yang paling sering idiopatik. Pada anak, biasanya bersifat akut dan dapat mengancam jiwa. Terapi lini pertama AIHA adalah kortikosteroid dan imunoglobulin. Respons paling baik terhadap steroid didapatkan pada anak. Autoimmune hemolytic anemia (AIHA) is caused by autoantibodies against own erythrocytes leading to hemolysis and anemia. The most common cause is idiopathic. In children, this anemia is usually acute and can be life-threatening. First line therapy is corticosteroid and can be combined with intravenous immunoglobulin. Best response to steroids is among children.